2017
DOI: 10.1371/journal.pone.0172281
|View full text |Cite|
|
Sign up to set email alerts
|

Do family and neighbourhood matter in secondary school completion? A multilevel study of determinants and their interactions in a life-course perspective

Abstract: BackgroundCompletion of secondary education is important for individuals’ future health and health behaviour. The fundamental purpose of this study is to investigate the variation and clustering of school completion in families and neighbourhoods. Secondly, we aim to examine the impact of individuals’ family structure and neighbourhood of residence and examine to what extent parental education level moderates these associations.MethodsLongitudinal register data for 30% of the entire Norwegian population aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Another reason strongly supporting early diagnosis is that it is easier to involve children and adolescents in treatment when parental support is available, than later on in young adulthood when such support might be harder to come by. Moreover, in cases of inadequate family background, school professionals might help children and adolescents to access treatment, directly in the school environment [5,25,26]. Because children and adolescents do not seek professional help for fear of stigmatization and lack of confidentiality [15,52], that underlines the importance to communicate on mental health services to defuse prejudices.…”
Section: Pan Et Al Demonstrated a Direct Link Between Academicmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason strongly supporting early diagnosis is that it is easier to involve children and adolescents in treatment when parental support is available, than later on in young adulthood when such support might be harder to come by. Moreover, in cases of inadequate family background, school professionals might help children and adolescents to access treatment, directly in the school environment [5,25,26]. Because children and adolescents do not seek professional help for fear of stigmatization and lack of confidentiality [15,52], that underlines the importance to communicate on mental health services to defuse prejudices.…”
Section: Pan Et Al Demonstrated a Direct Link Between Academicmentioning
confidence: 99%
“…Depending on the study, school difficulties are operationalized differently and include different variables, such as academic failure, inappropriate behavior at school or absenteeism. These manifestations are not only indirect predictors of current or future mental health difficulties, but also, as highlighted in several studies, may as well be associated with past family difficulties and early-life adversity [19,25,26].…”
mentioning
confidence: 94%
“…School non-completers are also far more likely to receive DP [ 10 , 11 , 19 ] or depend on other medical and non-medical public benefits early in life [ 10 , 11 , 20 ]. Moreover, numerous studies have shown that childhood adversities, such as parental disability and low socioeconomic status, are associated with physical and mental health problems [ 21 27 ], low educational achievement [ 28 , 29 ] and work disability [ 10 , 30 , 31 ] later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Several social dimensions influence educational achievement and may contribute to generate educational inequalities (Støren and Helland, 2009; Bäckman and Nilsson, 2010; Myhr et al, 2017). We have selected the following demographic and socioeconomic determinants to evaluate their effects on the probability of completing secondary education among the Norwegian youth population.…”
Section: Methodsmentioning
confidence: 99%
“…Family origin and a family’s resources and strategies create a powerful social context that to a large extent predicts educational achievement (Corrás et al, 2017). Factors shown to be associated with youth non-completion of secondary education include low parental socioeconomic status (SES) and family adversity such as parental divorce, household instability, and poverty (Amato, 2001; De Ridder et al, 2013; Myhr et al, 2017). Adolescents who drop out of secondary education are substantially reducing their odds of having long, happy, and healthy lives (Viner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%